THE EFFECT OF FINANCIAL LITERATURE ON THE FINANCIAL MANAGEMENT OF MSMES - Ade Gunawan; Hanifa Zihan Safira (International Journal Reglement & Society (IJRS), 2022)
This research is a quantitative research. The purpose of this study was to determine the effect of financial literacy on the financial management of SMEs in Medan Selayang. The sample in this study were 35 MSME business actors in Medan Selayang District. The analytical technique in this research is a simple linear analysis technique. The research results show thatFinancial literacy affects financial managementSMEs inOverview.The magnitude of the influence of financial literacy on village financial management is43.6% while the remaining 56.4% is explained by other variables that are not included in this research model.